The Role of Teachers as Facilitators and its Obstacles in Learning Implementation - Junaidi Junaidi; Nurhizrah Gistituati; Alwen Bentri (Postgraduate School, Universitas Negeri Padang, 2021)
2013 curriculum requires students as learning centres and teachers as facilitators in the implementation of learning. It means that the teachers arefacilities providers in the learning process. The teachers are the responsible ones who should create an atmosphere of conducive learning activities in compliance with students development. To implement that,the teachers have a role which should stimulate teaching and learning interactions. Thus, the teaching and learning interactionscan be effective and optimal. The role of facilitatorsis not easy for teachers. In the implementation of learning, there are various obstacles that arise from schools, teachers, and students. The obstacles that arisefrom schools are the lack of facilities and the lack of leaders’ responsibility. The obstaclesthat arise from teachersare the lack of understanding and competency to implement student-based learning activities, aside from the difficulty to change their old habits. The obstacle for students is their second nature to be lectured by teachers.